Effect of fiber diameter on flexural properties of fiber-reinforced composites - Mohammad Bagher Rezvani; Mohammad Atai; Faeze Hamze (Wolters Kluwer Medknow Publications, 2013)
Background: Flexural strength (FS) is one of the most important properties of restorative dental materials which could be improved in fiber-reinforced composites (FRCs) by several methods including the incorporation of stronger reinforcing fibers. Aim: This study evaluates the influence of the glass fiber diameter on the FS and elastic modulus of FRCs at the same weight percentage. Materials and Methods: A mixture of 2,2-bis-[4-(methacryloxypropoxy)-phenyl]-propaneand triethyleneglycol dimethacrylate (60/40 by weight) was prepared as the matrix phase in which 0.5 wt. % camphorquinone and 0.5 wt. % N-N'-dimethylaminoethyl methacrylate were dissolved as photoinitiator system. Glass fibers with three different diameters (14, 19, and 26 μm) were impregnated with the matrix resin using a soft brush. The FRCs were inserted into a 2 × 2 × 25 mm 3 mold and cured using a light curing unit with an intensity of ca. 600 mW/cm 2 . The FS of the FRCs was measured in a three-point bending method. The elastic modulus was determined from the slope of the initial linear part of stress-strain curve. The fracture surface of the composites was observed using scanning electron microscopy to study the fiber-matrix interface. Statistical Analysis: The results were analyzed and compared using one-way ANOVA and Tukey's post-hoc test. Results: Although the FS increased as the diameter of fibers increased up to 19 μm (P < 0.05), no significant difference was observed between the composites containing fibers with diameters of 19 and 26 μm. Conclusion: The diameter of the fibers influences the mechanical properties of the FRCs.